2021
DOI: 10.1007/978-3-030-72595-2_6
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation and Design of Kindergarten Outdoor Space and the Outdoor Activities: A Case Study of Kindergartens in Bergen, Norway and Anji in China

Abstract: Compared with Norwegian kindergartens that emphasize how outdoor activity benefits young children’s integrated development, Chinese kindergartens reluctantly encourage children to go outside for long time. A county named Anji in South China’s Zhejiang province has started to change this approach to outdoor play. Kindergartens there provide outdoor equipment to support children’s outdoor activities for longer periods of time. This approach is called Anji Play and has been recommended by Chinese Ministry of Educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…For example, slopes with different angles of inclination enable children to perceive different senses of space. Moreover, Anji Kindergarten provides a wide variety and quantity of low-structure materials for children to learn to explore [27]. The comprehensive and fresh game environment is full of excitement and challenges, which can greatly arouse children's interest in games, bring them positive emotional experiences and cultivate their spirit of adventure [28].…”
Section: Returning the Natural Play Environment To Young Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, slopes with different angles of inclination enable children to perceive different senses of space. Moreover, Anji Kindergarten provides a wide variety and quantity of low-structure materials for children to learn to explore [27]. The comprehensive and fresh game environment is full of excitement and challenges, which can greatly arouse children's interest in games, bring them positive emotional experiences and cultivate their spirit of adventure [28].…”
Section: Returning the Natural Play Environment To Young Childrenmentioning
confidence: 99%
“…Research has shown that both the moving and pleasant experiences of positive emotional experiences contribute significantly to creativity [30]. In the Anji game, children build their own fancy objects with various bamboo toys, crawl fearlessly on the tall climbing frame and play freely in the mud, which is enough to let children feel the great freedom and pleasure brought by the natural environment, thus stimulating creativity and enriching play experience [27].…”
Section: Returning the Natural Play Environment To Young Childrenmentioning
confidence: 99%